PENGARUH PEMBELAJARAN ACTIVE LEARNING POSTER COMMENT TERHADAP HASIL BELAJAR SISWA PADA KURIKULUM MERDEKA - Mufroda Alfiatun Nisa; Feri Tirtoni (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2023)
The purpose of this study to determine the effect of active learning poster comment learning outcomes of students in Grade IV-A on the independent curriculum contained in one of the primary schools in the District Krembung, to the subject matter of Pancasila “attitudes and actions according to the precepts of pancasila” to determine how much influence active learning poster comment learning outcomes of students. The population of this study was all students totaling 20 students, consisting of 9 male students and 11 female students. In this study using saturated samples, where all members of the population sampled. The research method is a quantitative method of Preexperiment and data processing using SPSS program. Based on the results of research and discussion, it can be concluded that the application of active learning poster comment has an influence on the learning outcomes of Pancasila students in the merdeka curriculum. From the results of filling the objective test shows that student learning outcomes improved after applying active learning poster comment compared to before applying active learning poster comment. From the results of the T-test hypothesis test shows that the mean Pretest is worth 55.10 and Posttest is worth 84.75 and the significance value is 0.00 < 0.05 which means the influence of active learning poster comment learning on the learning outcomes of Pancasila students in the independent curriculum. Abstrak Tujuan penelitian ini untuk mengetahui pengaruh pembelajaran active learning poster comment terhadap hasil belajar siswa kelas IV pada kurikulum merdeka yang terdapat pada salah satu sekolah dasar di Kecamatan Prambon, terhadap materi pelajaran Pancasila yang digunakan untuk mengetahui seberapa besar pengaruh pembelajaran active learning poster comment terhadap hasil belajar siswa. Populasi penelitian ini adalah seluruh siswa yang berjumlah 14 siswa, terdiri dari 12 siswa laki-laki dan 2 siswa perempuan. Dalam penelitian ini menggunakan sampel jenuh, dimana semua anggota populasi dijadikan sampel. Adapun metode penelitian ini adalah metode Kuantitatif PreEksperimen dan pengolahan data menggunakan program SPSS. Berdasarkan pada hasil penelitian dan pembahasan, sehingga dapat ditarik kesimpulan bahwa penerapan pembelajaran aktif poster comment terdapat pengaruh pada hasil belajar Pancasila siswa di kurikulum merdeka. Dari hasil pengisian tes obyektif menunjukkan bahwa hasil belajar siswa lebih meningkat setelah menerapkan active learning poster comment dibandingkan dengan sebelum menerapkan active learning poster comment. Dari hasil hipotesis Uji T-test menunjukkan bahwa mean Pretest bernilai 70,29 dan Posttest bernilai 88,29 dan pada nilai signifikansi 0,00 < 0,05 yang artinya adanya pengaruh pembelajaran active learning poster comment terhadap hasil belajar mata pelajaran Pancasila siswa pada kurikulum merdeka.